Revitalisasi Fikih Keluarga Sebagai Instrumen Pencegahan Kekerasan Seksual Pada Anak - Ismi, Nur; Kurniati, Kurniati; Marilang, Marilang (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The phenomenon of child sexual violence is becoming more frequent, children should receive special protection for their physical and mental health. This aims to ensure that children can grow and develop well and be protected from the threat of dangerous crimes in accordance with Law Number 35 of 2014 concerning Child Protection. Parents play an important role in preventing sexual violence against children, therefore knowledge and attitudes, as well as parental behavior towards sex education are very important. In this research, two main themes will be discussed, namely; the concept of parenting from a family jurisprudence perspective and the role of parents in preventing sexual violence against children from a family jurisprudence perspective. The question arises whether parents' parenting patterns for children have been regulated in Islamic law, and what is the correct parenting pattern according to family jurisprudence that can prevent sexual violence against children. This research uses the results of a literature search containing theories relevant to the research problem. In this research, an assessment was carried out regarding the concepts and theories used based on literature related to the topic and available. This research is descriptive research which focuses on a systematic explanation of the facts obtained when the research was conducted. From this research it can be understood; The concept of ḥaḍānah or care is explained in three general parts, namely regarding the requirements for a caretaker, the classification of people who have custody, and the length of the care period. The role of parents and family is an important part of the social environment which is needed as a center for children's development towards sexual maturity. Parents must understand and convey sex education to their children. Among the efforts to prevent sexual violence against children are training children to ask permission before entering their parents' room, separating children's beds, getting children used to lowering their eyes and covering their private parts, as well as several other methods which will be explained by the author.